Effect of Manual Guidance Versus Knowledge of Performance in Weight Bearing Skill Training of Different Durations Among Young Healthy Subjects Using Bathroom Scale – A Comparative Study: Life Sciences-Physiology - Purkayastha, Moushami; Sarma, P.C; Muthukaruppan, Sankar Sahayaraj (International Journal of Life Science and Pharma Research, 2022)
Distribution of body weight is a significant factor influencing Postural Stability and is one of the measures of balance, to quantify the extent of deficiency in Postural Control of stroke survivors. The study aims to compare the effectiveness of manual guidance and knowledge of performance in healthy subjects and the objective assessed was 70 % of weight bearing skill on the dominant limb at three different durations of post10 minutes, post 15 days and post one month of practice. Sixty subjects participated in the study and were randomly allocated into two groups and assigned the task of distributing their weight at a 70:30 ratios between their feet, which was tested for the ability of Retention in: Ten Minutes, 15 Days, and one month of practicing. Both the groups were analyzed depending on Manual Guidance and Knowledge of Performance received, respectively, and found to demonstrate significant differences (p<0.01). Group analysis was done using one-way ANOVA. These study advocates for both manual guidance and knowledge of performance as an effective mode of training the young healthy subject’s symmetrical weight bearing skill. However, knowledge of performance is comparatively more effective in retaining the learned skills as compared to manual guidance. So in the long after term when the goal is long term, utilization of knowledge of performance will prove more effective in motor skill training. Keywords: , , , ,